On the basis of art 150 years of women at Yale - Cooper, Helen A.; Kramer, Linda Konheim 1939-; Kuzma, Marta 1964- (Yale University Art Gallery, 2021)
A tribute to the impressive roster of women artists who have graduated from Yale University. Marking the 150th anniversary of the first women students at Yale, who came to study at the Yale School of the Fine Arts (now Yale School of Art) when it opened in 1869, and the 50th anniversary of undergraduate coeducation at the University, this volume honors the accomplishments of women artist-graduates of Yale. More than 80 artists-including Rina Banerjee, Janet Fish, Audrey Flack, Eva Hesse, Maya Lin, Sylvia Plimack Mangold, Howardena Pindell, and Mickalene Thomas-are represented with works drawn exclusively from the Yale University Art Gallery. Essays and timelines detail related milestones such as the appointment of art historian Anne Coffin Hanson as the first woman to be hired as a full, tenured professor on campus and Mimi Gardner Gates as the first female director of the Gallery. Amid the rise of feminist movements-from women's suffrage to the #MeToo movement of today-this book asserts the crucial role women have played in pushing creative boundaries at Yale, and in the art world at large. Exhibition: Yale University Art Gallery (10.8.2021-9.1.2022)
Letzte Seite: Published in conjunctionwith the exhibition "On the Basis of Art: 150 Years of Women at Yale", organized by the Yale University Art Gallery. September 10, 2021-January 9, 2022
Keywords: Yale University -- School of Art and Architecture; Geschichte 1869-2021; Kunststudium; Künstlerin; Frau; Yale University / School of Art / Students; Yale University / Students; Yale University; Women artists / Connecticut / New Haven / Exhibitions; Women artists / Education / Connecticut / New Haven; Students; Women artists; Exhibition catalogs; Connecticut; New Haven; Ausstellungskatalog -- Yale University Art Gallery -- 10.8.2021-9.1.2022 -- New Haven